Journey of the universe - Swimme, Brian (Yale University Press, 2011)
"Today we know what no previous generation knew: the history of the universe and of the unfolding of life on Earth. Through the astonishing combined achievements of natural scientists worldwide, we now have a detailed account of how galaxies and stars, planets and living organisms, human beings and human consciousness came to be. And yet . . . we thirst for answers to questions that have haunted humanity from the very beginning. What is our place in the 14-billion-year history of the universe? What roles do we play in Earth's history? How do we connect with the intricate web of life on Earth? In Journey of the Universe Brian Thomas Swimme and Mary Evelyn Tucker tell the epic story of the universe from an inspired new perspective, weaving the findings of modern science together with enduring wisdom found in the humanistic traditions of the West, China, India, and indigenous peoples. The authors explore cosmic evolution as a profoundly wondrous process based on creativity, connection, and interdependence, and they envision an unprecedented opportunity for the world's people to address the daunting ecological and social challenges of our times. Journey of the Universe transforms how we understand our origins and envision our future. Though a little book, it tells a big story one that inspires hope for a way in which Earth and its human civilizations could flourish together. This book is part of a larger project that includes a documentary film, an educational DVD series, and a website. The film and the DVD series will be released in 2011. For more information, please consult the website, journeyoftheuniverse.org"--